Phylogenetic Affinities of Acanthopleurinae Dall, 1889 Chitons (Mollusca: Polyplacophora: Chitonidae) from Jazan Coast in the Red Sea and Western Indo-Pacific - Hassien Alnashiri; Liju Thomas; Maqbool Thaikkottathil; Siby Philip; Ranjeet Kutty; Sureshkumar Sivanpillai; Ali Mohammed Abo Rasain (Journal of Marine Science and Engineering, 2023)
Chitons (Polyplacophora) are marine molluscs that mostly inhabit rocky intertidal shores. Their biological and phylogenetic studies are comparatively sparse in the western Indo-Pacific regions. In addition, chitons belonging to the subfamily Acanthopleurinae Dall, 1889, collected from the Andaman Sea of the northeastern Indian Ocean and the Jizan coast of Saudi Arabia were sequenced and analyzed to study the phylogenetic affinities. The analysis was carried out using a single locus dataset (cytochrome oxidase 1) generated during the present study and integrated with sequences retrieved from GenBank. Acanthopleura gemmata (Blainville, 1825) from India was linked to Acanthopleura vaillantii Rochebrune, 1882, from the Saudi Arabia coast. Squamopleura miles (Carpenter in Pilsbry, 1893) from the Indian coast forms a separate clade representing the genus. Furthermore, the results illustrate several significant instances of misplacement of several species under the wrong genus and the existence of cryptic species within the genera Acanthopleura and Squamopleura. An integrated approach is required to better understand these important intertidal groups’ taxonomy, systematics, and biogeography.